Factors affecting the application of international financial reporting standard on financial instruments in banks - Quynh, Huong Nguyen Thi; Kim, Oanh Vu Thi (Edelweiss Applied Science and Technology, 2025)
The International Financial Reporting Standard (IFRS) is a global accounting language adopted in over 160 countries. The research illuminates the level of IFRS application on financial instruments at Vietnamese commercial banks and explores the impact factors of the IFRS transition. The study is based on data collected from accounting staff and chief accountants working in 28 Vietnamese commercial banks during February 2024. Besides the qualitative method (expert survey), the research uses Principal Component Analysis and logistic regression analysis to test the impacts of factors on IFRS implementation. The findings show that the legal accounting system, the capacity of accountants, the implementation staff, financial capacity, and information technology are the five decisive factors affecting the IFRS application in Vietnam, while the development of the market and the support of managers do not show significant impacts on the implementation of IFRS. The results are of great importance as 2025 is the milestone for commercial banks in Vietnam to apply IFRS. The insights from the research suggest that commercial banks adopt appropriate strategies to successfully apply IFRS on financial instruments.